The role of comorbidity in the development of Long-COVID - T.V. Chernii; V.I. Chernii; D.A. Fokina (Civic Union "Communicable Diseases Intensive Care Association", 2023)
BACKGROUND. Post-COVID syndrome is a set of conditions that occur in patients after a coronavirus infection. To date, there remains great interest in identifying the relationships between the influence of concomitant diseases on the course of SARS-CoV-2 infection and the selection of a justified treatment regimen from the point of view of the pathogenesis of the formation of long-term consequences of the disease. OBJECTIVE. To investigate the role of comorbidity in the development of Long-COVID, to study and analyze the results of treatment with a combination of Xavron, Tivorel and Xylate in patients with asthenic manifestations of Long-COVID. MATERIALS AND METHODS. A clinical and neurological examination of 50 patients aged 47 to 76 years with a diagnosis of chronic cerebral ischemia and an asthenic syndrome that persisted for more than 3 months after a confirmed SARS-CoV-2 infection was carried out. All patients were treated according to a clinical protocol approved by the MOH of Ukraine. In addition to the main treatment, 20 patients received a 10-day course of infusions of a combination of the drugs Xavron in a dose of 30 mg No. 10, Tivorel 100.0 No. 5 and Xylate 200.0 No. 5 every other day. Efficacy was assessed before treatment, on the 5th and 10th day of treatment using the MMSE, DASS-21, FAS and MOND scales. RESULTS AND DISCUSSION. A stable positive relationship was found between the number of CIRS-G comorbidity scores and the MOND score. A positive correlation coefficient between comorbidity and asthenic syndrome, assessed on the FAS scale, was also expressed - 0.699 (p<0.001). A somewhat weaker negative relationship was found between anxiety and the number of points on the CIRS-G scale - -0.474 (p=0.035). Assessment of depression and stress on the DASS-21 scale did not show a reliably significant correlation effect. After treatment, the severity of neurological symptoms, assessed by the MOND scale, decreased from 5.6±1.6 to 2.8±1 (p<0.01). Depression and anxiety scores on the DASS-21 scale decreased moderately from 4.9±3.6 to 2.8±1.5 (p<0.01) and from 6.3±2.3 to 4.3±1.5 (p<0.01), respectively. A more significant regression was observed on the stress scale - from 10.3±3.1 to 7.5±1.9 (p<0.01). The difference in the severity of fatigue from 28.8±4.1 to 20±1.2 was especially noticeable (p<0.01). CONCLUSIONS. Asthenic syndrome, which is prevalent in the Long-COVID, directly depends on the background of chronic diseases. The combination of Xavron, Tivorel and Xylate is pathogenetically justified and safe in the treatment of patients with Long-COVID. The use of this combination leads to a reduction of asthenic syndrome, which, in turn, has a positive effect on the reduction of cognitive manifestations of Long-COVID in the form of "brain fog".